Physician–Pharmacist Collaborative Clinic Model to Improve Anticoagulation Quality in Atrial Fibrillation Patients Receiving Warfarin: An Analysis of Time in Therapeutic Range and a Nomogram Development - Wang, Na; Qiu, Sha; Yang, Ya; Zhang, Chi; Gu, Zhi-Chun; Qian, Yan (Frontiers in Pharmacology, 2021)
Background: Poor time in therapeutic range (TTR) control is associated with an increased risk of stroke and bleeding in atrial fibrillation (AF) patients receiving warfarin. This study aimed to determine whether the physician–pharmacist collaborative clinic (PPCC) model could improve the anticoagulation quality as well as to create a nomogram for predicting anticoagulation quality in AF patients. Methods: This retrospective observational study enrolled AF patients who either initially received warfarin or returned to warfarin after withdrawal between January 1, 2016 and January 1, 2021, at our institution. The primary outcome was dynamic changes in TTRs. The secondary outcomes were thromboembolic and bleeding events during follow-up. We compared the dynamic changes in TTRs between the general clinic (GC) and PPCC groups in both the original and propensity score matching (PSM) cohorts. In addition, we explored the potential predictors of high anticoagulation quality and subsequently formulated a nomogram to predict anticoagulation quality. Results: A total of 265 patients with AF were included, comprising 57 patients in the PPCC group and 208 patients in the GC group. During a median follow-up period of 203 days, the PPCC group had a shorter time (76 days vs. 199 days, P < 0.001) and more patients achieved a TTR ≥ 60% (73.7% vs. 47.1%, P = 0.002 by log-rank test) than the GC group. The results from the PSM cohort confirmed this finding. No significant differences in the incidences of thromboembolic events (5.3% vs. 5.3%, P = 1.000) and bleeding events (4.3% vs. 3.5%, P = 1.000) were observed between the two groups. Four variables were explored as predictors related to high anticoagulation quality: treatment within a PPCC, history of bleeding, history of bleeding, and the presence of more than four comorbidities. The nomogram revealed a moderate predictive ability (c-index: 0.718, 95% confidence interval (95%CI): 0.669–0.767) and a moderately fitted calibration curve. Conclusions: The PPCC model contributed to improved anticoagulation quality in AF patients receiving warfarin. The nomogram might be an effective tool to predict anticoagulation quality and could aid physicians and pharmacists in the selection of patients who will likely benefit from sustained and active intervention.